2018
DOI: 10.1136/bmjopen-2017-018164
|View full text |Cite
|
Sign up to set email alerts
|

Did case-based payment influence surgical readmission rates in France? A retrospective study

Abstract: ObjectivesTo determine whether implementation of a case-based payment system changed all-cause readmission rates in the 30 days following discharge after surgery, we analysed all surgical procedures performed in all hospitals in France before (2002–2004), during (2005–2008) and after (2009–2012) its implementation.SettingOur study is based on claims data for all surgical procedures performed in all acute care hospitals with >300 surgical admissions per year (740 hospitals) in France over 11 years (2002–2012; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A previous study in France examined the risk of readmission within 30 days and the trends in patients from different MDCs before and after implementing a DRG-based payment system [ 45 ]. They found that as time progressed, ophthalmology gradually became the disease category with the highest risk of readmission within 30 days, while obstetric and gynecological diseases also had a higher risk of readmission within 30 days than other disease categories [ 45 ]. Our study also found that patients with Diseases and Disorders of the Skin, Subcutaneous Tissue, and Breast (MDC9) had the second-highest risk of readmission within 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in France examined the risk of readmission within 30 days and the trends in patients from different MDCs before and after implementing a DRG-based payment system [ 45 ]. They found that as time progressed, ophthalmology gradually became the disease category with the highest risk of readmission within 30 days, while obstetric and gynecological diseases also had a higher risk of readmission within 30 days than other disease categories [ 45 ]. Our study also found that patients with Diseases and Disorders of the Skin, Subcutaneous Tissue, and Breast (MDC9) had the second-highest risk of readmission within 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that their effects tend to be greatest during the initial implementation period and stabilize or dissipate over time. 4 Research has documented increased readmissions in Switzerland 44 and France, 10 suggesting that more research on the long-term association of DRGs with quality of care is warranted. Second, our data only included readmissions and deaths in public hospitals; readmissions to private hospitals and deaths outside public hospitals were not captured.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 , 6 , 7 , 8 Reductions in length of stay have generally been observed after the introduction of DRGs, whereas evidence on volume of care and other quality indicators is mixed. 2 , 6 , 9 , 10 Some studies have attributed variations in the consequences of DRGs to health care system factors. Busse et al 2 suggested that DRGs were associated with an increase in volume of care when replacing a global budget system but with a decrease when replacing a fee-for-service system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These analysis results show that DRG standardized price systems are not immune to political pressure. Vuagnat et al ( 27 ) studied the impact of the implementation of a case-based payment system on postoperative readmission. The results showed that the rate of readmission in the private and public sectors increased relatively steadily and did not seem to be affected by the case-based payment system.…”
Section: Introductionmentioning
confidence: 99%